Analysis of Customer Knowledge, Halal Brand, Trust, and Customer Engagement on Customer Loyalty at PT Bank Syariah Indonesia in Semarang - Alya Maherka Ekaputri; Mustika Widowati; Sri Hardiningsih H.S (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
This study aims to analyze the significance effect of Customer Knowledge, Halal Brand, Trust, and Customer Engagement on Customer Loyalty on PT Bank Syariah Indonesia in Semarang both simultaneously and partially. The used data is primary data which collected by using questionnaire. Population in this study were all customer PT Bank Syariah Indonesia in Semarang, while the sample in this study was 115 participants customer PT Bank Syariah Indonesia in Semarang. Sampling is using a purposive sampling technique. The analysis model used in this research is multiple regression analysis, and the analysis technique uses the simultaneously significant test, determination correlation test, and partial significance test with the SPSS 25.00. The results of proving the hypothesis and discussion show that Customer Knowledge, Halal Brand, Trust, and Customer Engagement simultaneously have a significant effect on Customer Loyalty PT Bank Syariah Indonesia in Semarang. Customer Knowledge and Trust partially have positive and insignificant effect on Customer Loyalty, whereas Halal Brand and Customer Engagement partially have positive and significant effect on Customer Loyalty at PT Bank Syariah Indonesia in Semarang.Keywords: Customer Loyalty, Customer Knowledge, Halal Brand, Trust, and Customer Engagement.